2021
DOI: 10.3390/app11083358
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Intensity of Postendodontic Pain and Flareup in Single and Multiple Visit Root Canal Treatments: A Systematic Review and Meta-Analysis

Abstract: To assess the incidence and intensity of postendodontic pain and flareup in single and multiple visit root canal treatment (RCT) and determine if the difference between the two is significant, a search of PubMed, Medline, Embase, Cochrane, Scopus and Web of science was conducted. The grey literature was searched using Google Scholar and Saudi digital library. Randomised controlled trials evaluating the incidence and intensity of postendodontic pain and flareup published in English from 1 January 2000 to 15 Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(104 reference statements)
0
16
1
Order By: Relevance
“…Studies suggest an insertion period of 2–4 weeks, when using calcium hydroxide [ 29 ]. A new review recommends deciding for or against multiple sessions, depending on the individual case, since no advantages for one particular type of session were found with regard to the incidence and intensity of pain [ 30 ]. Obturation was performed using cold lateral condensation which has been, for years, the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest an insertion period of 2–4 weeks, when using calcium hydroxide [ 29 ]. A new review recommends deciding for or against multiple sessions, depending on the individual case, since no advantages for one particular type of session were found with regard to the incidence and intensity of pain [ 30 ]. Obturation was performed using cold lateral condensation which has been, for years, the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…In the Vishwanathaiah S. et al review, in the majority of analyzed studies there were no significant differences in the occurrence of PEP between the single and multiple visit RCT [ 57 ]. One of the authors’ observations was that the studies conducted after April 2020 found no significant difference between the two procedures, in contrary to older studies [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used a numerical rating scale (NRS) and nonspecified questionnaires, whilst the visual analogue scale (VAS), which is more sensitive than other pain scales (Price et al, 1994), was used in few studies. This lack of standardization in reporting pain is a major problem for meta-analysis in systematic reviews reporting on endodontic pain (Vishwanathaiah et al, 2021). There are many other patient-reported outcomes such as cost effectiveness of treatment and satisfaction with treatment which are not reported in most of the studies.…”
Section: Summary Of Evidencementioning
confidence: 99%